1996
DOI: 10.1111/j.1365-3180.1996.tb01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Precision of soil seedbank sampling: how many soil cores?

Abstract: Summary A prerequisite for a precise estimate of the abundance of weed seeds in sou is prior knowledge of sampling variability, Based on an analysis of EWRS working group trials, it is shown that the sampling variance (s2) of seed counts increases with the sampling mean (S2) and can be predicted with the logarithmic form of Taylor's power law: log10(sz)=a+b log10(x̄). This relationship is constant over time for means greater than 0.1 seeds per core within each of the five different sites studied (temporal vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
1
37
1
5
Order By: Relevance
“…, * Correspondance et tirés à part même dans les régions où le désherbage chimique est régulièrement pratiqué depuis de nombreuses années (Roberts et Chancellor, 1986 ;Barralis et Chadœuf, 1987 ;Zanin et al, 1992 Salin, 1973 ; Ricketts, 1979 ;Roberts, 1981 ;Beuret, 1984 ;Roberts, 1984 ;Lambelet-Haueter, 1986 ;Barralis et Chadœuf, 1988 ;Debaeke, 1988b ;Ball et Miller, 1989 ; Lawson, 1992 ; Aebischer, 1995), ce taux ayant tendance à être plus élevé chez les graminées que chez les dicotylédones (Forcella et al, 1992). La (Moss, 1988 ;Dessaint et al, 1996a) est bien connu, et le taux de levée est d'autant plus faible que les semences sont profondément enfouies (Roberts et Feast, 1972 ;Froud-Williams et al, 1984).…”
unclassified
“…, * Correspondance et tirés à part même dans les régions où le désherbage chimique est régulièrement pratiqué depuis de nombreuses années (Roberts et Chancellor, 1986 ;Barralis et Chadœuf, 1987 ;Zanin et al, 1992 Salin, 1973 ; Ricketts, 1979 ;Roberts, 1981 ;Beuret, 1984 ;Roberts, 1984 ;Lambelet-Haueter, 1986 ;Barralis et Chadœuf, 1988 ;Debaeke, 1988b ;Ball et Miller, 1989 ; Lawson, 1992 ; Aebischer, 1995), ce taux ayant tendance à être plus élevé chez les graminées que chez les dicotylédones (Forcella et al, 1992). La (Moss, 1988 ;Dessaint et al, 1996a) est bien connu, et le taux de levée est d'autant plus faible que les semences sont profondément enfouies (Roberts et Feast, 1972 ;Froud-Williams et al, 1984).…”
unclassified
“…They assert that in species occurring irregularly, a too high number of partial samples is needed, which is technically impossible. Another authors, Goyeau and Fablet (1982), Zanin et al (1989), Dessaint et al (1992Dessaint et al ( , 1996, based on statistical analyses, found that the necessary number of partial samples depended on the number of weed seeds per m 2 , i.e. the number of partial samples can be reduced at increasing amount of seeds.…”
Section: The Minimum Number Of Taken Samplesmentioning
confidence: 99%
“…the number of partial samples can be reduced at increasing amount of seeds. Dessaint et al (1990Dessaint et al ( , 1996 state that it is necessary to estimate hundreds of samples to achieve reliable results about numbers of weed seeds in soil. By contrast, according to Forcella et al (1992), it is sufficient to take 10 to 20 partial samples per plot (field) at the diameter of 5.0 cm or about 25 partial samples at the diameter 2.5 cm to obtain reliable results.…”
Section: The Minimum Number Of Taken Samplesmentioning
confidence: 99%
“…56 2011 54 et al 1986 ;Zanin et al 1989 ;Ambrosio et al 1997 ;Jones 1998 Barralis et al 1986 ;Lopez et al 1988 ;Chauvel et al 1989 ;Zanin et al 1989 ;Dessaint et al 1990Dessaint et al , 1996Ambrosio et al 1997, Barralis et al 1986Lopez et al 1988 ;Zanin et al 1989 ;Dessaint et al 1990Dessaint et al , 1996 …”
Section: Barralisunclassified